The Immediate Effects of Intermittent Theta Burst Stimulation of the Cerebellar Vermis on Cerebral Cortical Excitability During a Balance Task in Healthy Individuals: A Pilot Study - Tan, Hui-Xin; Wei, Qing-Chuan; Chen, Yi; Xie, Yun-Juan; Guo, Qi-Fan; He, Lin; Gao, Qiang (Frontiers in Human Neuroscience, 2021)
Objective: This pilot study aimed to investigate the real-time effects of single-session intermittent theta-burst stimulation (iTBS) of the cerebellar vermis on changes in cerebral cortical excitability in healthy individuals through a balance task. Subjects: A total of seven right-handed healthy subjects (26.86 ± 5.30 years) were included in this study. Interventions: Each subject received single-session iTBS of the cerebellar vermis in the sitting position. Main measures: Before and after the intervention, all subjects were asked to repeat the balance task of standing on the left leg three times. Each task consisted of 15 s of standing and 20 s of resting. Real-time changes in cerebral cortex oxygen concentrations were monitored by functional near-infrared spectroscopy (fNIRS). During task, the changes in blood oxygen concentration were collected and converted into the mean HbO2 for statistical analysis. Results: After stimulation, HbO2 values in the bilateral supplementary motor area, S15-D15 in the left cortex (P = 0.029) and S12-D14 (P = 0.043) in the right cortex were significantly increased. However, no significant change in mean HbO2 was found in the bilateral dorsolateral frontal lobe (P > 0.05). Conclusions: iTBS of the cerebellar vermis can increase the excitability of the cerebral cortex in the bilateral supplementary motor area during balance tasks. (Chinese Clinical Trial Registry: ChiCTR2100048915)